The preventative benefit of group diversification on group performance decline: An investigation with latent growth models. (24th January 2021) - Li, Jia; Shemla, Meir; Wegge, Jürgen
Summary: Integrating the open systems perspective of groups and the contingency approach to diversity, we study how group diversification (i.e., a process in which a group becomes more diverse over time as members join and/or leave the group) affects group performance change in an adverse task environment. We argue that diversification benefits performance by reducing group performance decline in times of adversity. Group size increase, however, attenuates this preventative benefit of group diversification. Focusing on organizational tenure and gender, we studied 279 sales groups (3277 individuals) in a large German financial consulting company from 2004 to 2008. In this period, a national legislative change prompted the company to withdraw its star product from the market and presented adversity to the sales groups. Results from latent growth models (LGMs) overall support our arguments. This research extends the (conditional) beneficial view of diversity from a static theoretical space about group being diverse to a dynamic one about group becoming diverse.